Letter to the Editor Response: Exploring COVID-19 Vaccine Hesitancy Among Stakeholders in African American and Latinx Communities in the Deep South Through the Lens of the Health Belief Model. Issue 5 (June 2023) - Bateman, Lori B.; Hall, Allyson G.; Anderson, William A.; Cherrington, Andrea L.; Helova, Anna; Judd, Suzanne; Kimberly, Robert; Oates, Gabriela R.; Osborne, Tiffany; Ott, Corilyn; Ryan, Melissa; Strong, Christian; et al.
The purpose of this submission to respond to a Letter to the Editor recently submitted regarding our manuscript, "Exploring COVID-19 Vaccine Hesitancy among Stakeholders in African American and Latinx Communities in the Deep South through the Lens of the Health Belief Model" published in the American Journal of Health Promotion in February, 2022. The manuscript reported on a study that had as its purpose to qualitatively explore perceptions related to COVID-19 vaccination intention among African American and Latinx participants and suggest potential intervention strategies.